Interview with Maria Vizcaíno Gómez - José Siles González; María del Carmen Solano Ruiz (Universidad de Alicante, 2018)
In this brief interview with a specialist in gynecology member of the commission of monitoring of Female Genital Mutilation in the Valencian Community, are treated essential aspects of Female Genital Mutilation and especially its incidence in the context of the Valencian Community.